Study on The Anti-Inflammatory Effects of Callicarpa nudiflora Based on The Spectrum–Effect Relationship - Li, Yamei; Yang, Yifang; Kang, Xingdong; Li, Xiaofeng; Wu, Yongzhong; Xiao, Junping; Ye, Yang; Yang, Jianqiong; Yang, Yang; Liu, Hai (Frontiers in Pharmacology, 2022)
Callicarpa nudiflora (C. nudiflora) is widely used as a big brand of Li nationality medicine with Hainan characteristics. C. nudiflora mainly contains phenylethanol glycosides, flavonoids, triterpenes, diterpenes, iridoid glycosides, volatile oils, and other small molecules, which exhibits multiple pharmacological activities including anti-bacteria, anti-inflammatory, hemostasis, antithrombotic and anti-tumor. However, it is difficult to screen out its anti-inflammatory active substances from these compounds. In this paper, the anti-inflammatory effects of C. nudiflora extracts were assessed by the inflammation model of rats, and the underlying mechanisms were also identified in vitro. High-performance liquid chromatography (HPLC) was used to establish the fingerprint of the C. nudiflora extracts, and twenty-two peaks were screened out. the anti-inflammation of C. nudiflora extracts were evaluated by the experiment of foot swelling in inflammatory rats. Afterward, the spectrum-effect relationship between the fingerprints and anti-inflammatory activities were researched by Pearson analysis and Orthogonal Partial Least Squares (OPLS) analysis to identify anti-inflammatory of C. nudiflora extracts. The differences of these extracts are illustrated by PCA and cluster analysis in pharmacological effects. As the results, twelve compounds were determined to catalpol(P1), caffeic acid(P2), protocatechuic acid(P9), 3,4-Dihydroxybenzaldehyde(P10), forsythiaside E(P12), protocatechualdehyde isomers(P14), forsythiaside B(P15), rutin(P16), alyssonoside(P21), verbascoside(P22), 2'-acetyl forsythoside B(P24) and isorhamnetin(P32) by HPLC-DAD and UPLC-Q-TOF MS/MS, were selected as potential compounds for anti-inflammatory activity in C. nudiflora. Particularly six compounds were identified as active substances with the greatest anti-inflammatory potential. Moreover, all compounds were tested for anti-inflammatory experiments or for anti-inflammatory literature retrieval. The results showed that the twelve compounds as bioactive compounds displayed with anti-inflammatory. In this study, a method for rapid screening of anti-inflammatory active ingredients in C. nudiflora was established, which can provide a reference for the future study of active compounds of C. nudiflora.